國小學生字母朗讀流暢度電腦化測驗之編製與發展 Developing a Computer-Based English Letter Naming Fluency Test for Primary School Students in Taiwan - 劉佩雲 Pei-Yun Liu; 吳玉珍 Yuh-Jen Wu (National Changhua University of Education, 2016)
字母知識是英語閱讀啟蒙教學的重要基礎能力之一，若未能及早具備精熟的字母辨識能力，後續在英語聽說讀寫的發展都會受到影響。為評估國小學童朗讀字母之正確率及流暢度，本研究旨在編製與發展國小學生英文字母朗讀流暢度電腦化測驗（Computer-based Letter Naming Fluency, C-LNF），並探討以C-LNF 作為臺灣學童早期英語閱讀能力發展篩檢工具的可行性。本研究以234 位國小一、二、三年級初學英語之學童為樣本，於第一年學習期末時進行電腦化及紙本版之LNF 測驗。研究發現，C-LNF 測驗信效度俱佳，其中信度方面，內部一致性Cronbach's α 係數為.98、折半信度為.98、三週後重測信度在正確率為.87，流暢度為.91，評分者一致性度為.99。效度部分採效標關聯效度，以DIBELS（Dynamic Indicators of Basic Early LiteracySkills）紙本版LNF 測驗為效標，參與者同時接受兩種版本施測，電腦化與紙本版之LNF 的相關在流暢度為.96，在正確率為.84，均達0.01 顯著水準，顯示C-LNF 具有 良好的信度與效度，可作為檢測國小學童字母朗讀能力之工具。本研究並依此工具取得初學英語學童第一年結束時應達到之英文字母朗讀數及切截點等參考數據，能提供英語教育工作者評估學童字母學習表現的有用參考。 One of the most fundamental skills in early English reading is the alphabet knowledge. Without mastering the alphabets, further development in English listening, speaking, reading, and writing will be obstructed. The current study aims to develop a computerbased letter naming fluency (C-LNF) measurement to assess novice English learners' ability in letter recognition and examined the applicability of C-LNF as a screening tool for early English literacy. The sample was 234 first-year English learners from Taiwan that include first-, second-, and third-graders. Their letter-naming ability were assessed twice at the end of first-year English learning in schools, one with computerbased tool and the other with paper-based measurement. C-LNF test exhibited acceptable reliability, with Cronbach's α .98, split-half reliability .98, three-week testretest reliability .87 for accuracy and .91 for fluency, and the inter-rater reliability .99. The criterion validity with paper-based DIBELS (Dynamic Indicators of Basic Early Literacy Skills) LNF test was .96 for fluency and .84 for accuracy, p<0.01. The results indicated that C-LNF is a qualified tool with proper technical adequacy that can be applied to assess letter naming ability in primary school students. Suggested letter naming fluency benchmark and cutoff points for students after one year of English learning were provided based on C-LNF which could serve as a valuable reference for English educators when evaluating students' performance in letter acquisition.